Recognizing boiled bone-remains from the Boca de Lega archaeological site in Argentina through mechanical spectroscopy studies - Lambri, Melania L.; Lambri, Osvaldo A.; Weidenfeller, Martin; Bozzano, Patricia B.; Bonifacich, Federico G.; Weidenfeller, Bernd; Lambri, Fernando D.; Zelada, Griselda I.; Rocchietti, Ana M. (Journal of Archaeological Science: Reports, 2023)
A study in thermo-altered bone-remains recovered from the Boca de Lega archaeological site (Santa Fe, Argentina) is performed with the aim of distinguishing among the whole group of seven investigated bone-remains which ones were boiled during culinary activities. In fact, for the boiled-bone-remains, the damping spectra exhibited the appearance of the damping peaks related to the loss of free water, the loss of the crystallization water, and the peak related to the viscous movement of collagen fibrils, after the triple helix to random coil transition; at around 370 K, 420 K and 510 K, respectively. In addition, the dynamic modulus behaviour in boiled samples exhibited the peaked shape behaviour as a function of temperature, i.e., an increase from around 370 K up to around 450 K, which was already reported for experimental bones. The results from mechanical spectroscopy were corroborated through scanning electron microscopy studies at high resolution. Besides, differential thermal analysis, thermogravimetry, and energy dispersive spectroscopy, are used also as instrumental techniques and their obtained results are discussed in the present work too.
CRIS-Team Scopus Importer:2023-04-07
Keywords: Boiled bone-remains; Cooking temperatures; Differential thermal analysis; Mechanical spectroscopy; Scanning electron microscopy; Thermo-altered bones; Thermogravimetry